Simulation of workpiece surface roughness after flat grinding by electroplated wheel - Mohammad Rabiey (2018)
The stochastic nature of grinding wheel topography together with grinding process parameters and kinematics have great influence on the surface roughness of workpiece. This paper aims to achieve a method of kinematics simulation of flat grinding process using MATLAB to predict the surface roughness of workpiece based on the topography of the electroplated Cubic Boron Nitride (CBN) wheel. Grain distribution, protrusion height and size are varied for each simulation. Based on trajectory of spherical grain forms in flat grinding kinematics, a 3D simulation of surface roughness is resulted. Suggestions are made for the improvement in accuracy of predicting workpiece profile.